Divergent neural substrates of inhibitory control in binge eating disorder relative to other manifestations of obesity. - Balodis, I; Molina, N; Kober, H; Worhunsky, P; White, M; Rajita Sinha; Grilo, C; Potenza, M (2013)
OBJECTIVE: An important endeavor involves increasing our understanding of biobehavioral processes underlying different types of obesity. The current study investigated the neural correlates of cognitive control (involving conflict monitoring and response inhibition) in obese individuals with binge eating disorder (BED) as compared to BMI-matched non-BED obese (OB) individuals and lean comparison (LC) participants. Alterations in cognitive control may contribute to differences in behavioral control over eating behaviors in BED and obesity. DESIGN AND METHODS: Participants underwent functional magnetic resonance imaging while completing the Stroop color-word interference task. RESULTS AND CONCLUSIONS: Relative to the OB and LC groups, activity in the BED group was differentiated by relative hypoactivity in brain areas involved in self-regulation and impulse control. Specifically, the BED group showed diminished activity in the ventromedial prefrontal cortex (vmPFC), inferior frontal gyrus (IFG), and insula during Stroop performance. In addition, dietary restraint scores were negatively correlated with right IFG and vmPFC activation in the BED group, but not in the OB or HC groups. Thus, BED individuals' diminished ability to recruit impulse-control-related brain regions appears associated with impaired dietary restraint. The observed differences in neural correlates of inhibitory processing in BED relative to OB and LC groups suggest distinct eurobiological contributions to binge eating as a subgroup of obese individuals.